Development of Portable Massage Bed - Dhavid Ramadhan Pratama; Selvi Atesya Kesumawati; Noviria Sukmawati; Bangkit Seandi Taroreh (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The development of various models of massage beds, ranging from simple to new innovations that provide more comfort and facilities that can be adjusted to your needs. The frequently used massage beds have a permanent shape, so they are difficult to carry and move when used. Portable massage beds are designed to make it easier to use from one location to another, save space, and can be adjusted according to the masseur's needs. This research aims to find out the specifications of portable massage bed products that are suitable for masseurs and patients. The sample in this study was a small scale trial of 6 masseurs at the massage clinic at Bina Darma University, Palembang, and subjects for a large scale trial were 10 people consisting of 6 masseurs and 4 patients at the massage clinic at Bina Darma University, Palembang. The stages of model development carried out are the model analysis, design and development (ADD) stages. The instrument used in this research was a questionnaire. The expert validity test results used the Content Validity Index (CVI) and Content Validity Ratio (CVR) with an average CVR value of 0.35. Based on the results of this research, it was found that the development of the portable massage bed model had good product quality as a place for patient massage. Then this model can be tested in the field on either a small or large scale (empirical validation).